Uncovering the Craft of Lyrics - Talhelm, Melissa (English Journal, 2021)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Weighted Vest - Furey, Rachel (River Styx, 2021)
Keywords: dept.eng; literary-work

Chytrid Fungus - Furey, Rachel (CALYX Journal, 2021)
Keywords: dept.eng; literary-work

Swimming - Furey, Rachel (Sou'wester, 2021)
Keywords: dept.eng; literary-work

A Dolphin in Pain - Furey, Rachel (Nimrod International Journal, 2021)
Keywords: dept.eng; literary-work

"A Charnel House of Uncertainty, Doubt, and Error": Medical and Narrative Authority in Some Fin-de-Siècle Fictions - Fluhr, Nicole (Literature and Medicine, 2021)
Keywords: dept.eng; peer-reviewed

At Home on the Stage: Toward an Affective Geography of Gentrification and Eviction in U.S. Cities - Stretch, Cynthia (Literary Representations of Precarious Work, 1840 to the Present, 2021)
Spoken word performance addressing gentrification and eviction encodes and embodies increasingly abstract and bureaucratically obfuscated processes of racialized dispossession in U.S. cities. Developing tropes across three works about housing precarity are read as poets’ attempts to identify the antagonists behind the digital wall of finance capital. Whereas the interactions of housing-insecure people with and within the housing market generate socially devalued identities, spoken word’s emphasis on “authenticity” requires poets to stand up as and for themselves as they wish to be (seen). In so doing, poets attempt to connect with audiences in real time to locate or reconstitute a stance as agents, however provisionally.
Keywords: A Scribe Called Quess?; Eviction; Gentrification; Nick Petrie; Roya Marsh; Spoken word poetry; dept.eng

Poisoning the Wells: Antisemitism in Contemporary America - Pessin, Andrew; Blackmer, Corinne E. (ISGAP, 2021)
Keywords: Antisemitism; United States; dept.eng; faculty_collection

The life and times of chinua achebe - Ogbaa, K. (2021)
The Life and Times of Chinua Achebe introduces readers to the life, literary works, and times of arguably the most widely-read African novelist of recent times, an icon, both in continental Africa and abroad. The book weaves together the story of Chinua Achebe, a young Igboman whose novel Things Fall Apart opened the eyes of the world to a more realistic image of Africa that was warped by generations of European travelers, colonists, and writers. Whilst continuing to write further influential novels and essays, Achebe also taught other African writers to use their skills to help their national leaders to fight for their freedoms in the post-colonial era, as internal warfare compounded the damage caused by European powers during the colonial era. In this book Kalu Ogbaa, an esteemed expert on Achebe and his works, draws on extensive research and personal interviews with the great man and his colleagues and friends, to tell the story of Achebe and his work. This intimate and powerful new biography will be essential reading for students and scholars of Chinua Achebe, and to anyone with an interest in the literature and post-colonial politics of Africa. © 2022 Kalu Ogbaa.
Keywords: dept.eng

The academy and publishing - Neverow, Vara (The Oxford Handbook of Virginia Woolf, 2021)
Keywords: dept.eng

Book Review: Stuart n. Clarke and david bradshaw (eds). Jacob’s room - Neverow, vara (The Review of English Studies, 2021)
Keywords: book.review; dept.eng

Landscape in Middle English Romance: The Medieval Imagination and the Natural World - Richmond, Andrew M. (Cambridge studies in medieval literature, 2021)
"In Sir Isumbras, one of the most enduringly popular late medieval romances, the penitential experience of its eponymous hero (modeled off of the evergreen St. Eustace tales) is grounded in a careful exploration of hillside ironmines and the communities of smiths that rely upon them. Such an interest in natural resource management and industrial development derives from the notable focus on charting topography that distinguishes the central third of the romance - marking Isumbras's transition from secular to divine systems of values, and his geographical movement from Christian to Saracen lands. Similarly, in the fourteenth-century Middle English version of William of Palerne (hereafter William), the eponymous protagonist flees with his lover, Melior, through a world of forests and bays that overflows with topographical details. These intricate explanations of quarry pits, hollow oaks, roadside groves, seaside caves, and war-torn estates together compose a perspective on landscape defined by networks of economic exchange. In this regard, the predominant view of the natural world presented in William ties it to earlier romances such as Havelok the Dane, a text interested in the systems of exchange that knit seaside fishermen to urban markets; and to later texts such as the Middle English versions of Partonope of Blois, which demonstrates in its depictions of estates the mercantile and agricultural uses of natural spaces that underlie the successful maintenance of a noble identity. This chapter, then, will discuss how Middle English romances' attention to the management and harvest of natural resources often reveals the link between country and urban spaces created by the exchange of such goods. I will also consider how sympathetic portrayals of laborers and other low-class harvesters of natural resources suggest that romances, particularly around the turn of the fifteenth century, reflect the shifting nature of their bourgeois-gentry audience by engaging with the environmental experiences of merchants, household clerks, reeves, franklins, and gentry farmers in addition to those of the higher aristocracy"--
Keywords: History and criticism; English literature; History and criticism; Landscapes in literature; Seashore in literature; Middle English, 1100-1500; Romances, English; SCSU Faculty Scholar Award; award_winner; dept.eng

La técnica del fluir de la conciencia joyceana como característica integral del canon literario argentino del siglo XX - Dirschel, Michael (Boletín de Literatura Comparada, 2021)
Keywords: dept.eng; peer-reviewed

Lord of the Forest | Good Fences - Sonnenschein, Dana (Kosmos Journal, 2021)
Keywords: dept.eng; peer-reviewed; ⛔ No DOI found

Meeting the Dire Wolf – Dana Sonnenschein - Sonnenschein, Dana (panoply, a literary zine, 2021)
Not just heavy bones. The huge skull fleshed, broad across the brow and muzzle, 3” canines, thick neck and body — the wolf of your nightmares and not just one.  Thirty. A pack drawn to the sce…
Keywords: dept.eng

Winter's Orphan - Sonnenschein, Dana (O:JA&L (Open: Journal of Arts & Letters), 2021)
Keywords: dept.eng; ⛔ No DOI found

Empirical insights into college students’ academic reading comprehension in the united states - Kalbfleisch, Elizabeth; Schmitt, Elena; Zipoli, Richard P. (Journal of College Reading and Learning, 2021)
This article reports on a collaborative research project involving faculty in writing studies, communication disorders, and applied linguistics that sought to empirically describe the reading skills of students (N = 910) in freshman composition classes at one college and two universities in the northeast United States. The research team developed and administered a questionnaire that evaluated students’ reading abilities according to six categories: inferential ability, background knowledge, general comprehension, vocabulary, figurative language/jargon, and morphosyntactic structures (grammar/syntax). Our statistically significant results showed that students scored best in the categories of background knowledge and general comprehension, which are well researched in a college population. However, students struggled in categories such as figurative language/jargon and morpho-syntactic structures, which are not well researched in a college population. Further, comprehension seemed generally discrete (understanding specific points of an essay) rather than holistic (indicated by an ability synthesize those points into a general statement about the author’s thesis). These findings suggest that further empirical research in this area will help describe the reading skills of college students and consequently will inform the development of pedagogical approaches that more effectively address students’ current needs. © 2021 College Reading and Learning Association.
Keywords: dept.cmd; dept.eng; dept.wll; peer-reviewed

Mistress of Snow - Sonnenschein, Dana (Gingerbread House Literary Magazine, 2021)
Hinges creak, and she swirls in the door, puts her finger to blue lips. Cold takes the old woodcutter, eyes open, breath frozen in his beard.  But crystals melt in your lashes as you gaze on her gl…
Keywords: dept.eng

The Lamb's New Song: Apocalypse in Early British Hymnody - Rosso, G. A. (Religion & Literature, 2021)
"The Lamb's New Song" argues that the Book of Revelation is the primary model for the Christ-centered liturgy of early Dissenting hymnbooks. In particular, the depiction of heavenly worship in Revelation, in which the slain Lamb is exalted to the throne of God and then sung a new song, is fundamental to the theology and symbolic vocabulary of the early British hymn. Dissenting writers in the 1690s drew on the Apocalypse to challenge the hegemony of the psalter in congregational worship, replacing the recital of scriptural psalms with the creation of new hymns to Christ. The essay features the work of Richard Davis, a controversial Independent minister whose Hymns Composed on Various Subjects (1694) anticipates Watts ground-breaking volume Hymns and Spiritual Songs (1707). Both writers foreground the christological drama at the heart of Revelation, in which the crucified and enthroned Lamb brings access to God, whose presence is made real during the public enactment of the hymn. The essay also challenges the influential theory of Stephen Marini, whose "Hymnody as History" (2002) posits an unbridgeable spiritual distance between the divine and human realms as a defining feature of eighteenth-century Anglophone hymns, a claim that fails to account for their central apocalyptic features. Putting early British hymnography in dialogue with New Testament studies can help show that British hymnists engaged with scriptural texts not simply as sources of doctrine and devotion but as fonts of inspiration and creativity.
Keywords: dept.eng; peer-reviewed